Kapitał społeczny a osiągnięcia szkolne ucznia - Radoła, Mirosław (Wydawnictwo Naukowe UAM, 2013)
The main goal of this article is to defi ne the relation between social capital and pupils’ educational achievements. The text also touches upon the subject of school selection. It defi nes the idea of social capital and shows its relation to pupils’ educational achievements. The authors make an attempt to formulate conclusions and postulates which appeared during the reading of literature and materials concerning research conducted in this area.
Social capital and pupils’ educational achievements
Keywords: social capital; school selection; pupils’ achievements